Selective targeting of chemically modified miR-34a to prostate cancer using a small molecule ligand and an endosomal escape agent - Ahmed M. Abdelaal; Ikjot S. Sohal; Shreyas G. Iyer; Kasireddy Sudarshan; Esteban A. Orellana; Kenan E. Ozcan; Andrea P. dos Santos; Philip S. Low; Andrea L. Kasinski (Elsevier, 2024)
Use of tumor-suppressive microRNAs (miRNAs) as anti-cancer agents is hindered by the lack of effective delivery vehicles, entrapment of the miRNA within endocytic compartments, and rapid degradation of miRNA by nucleases. To address these issues, we developed a miRNA delivery strategy that includes (1) a targeting ligand, (2) an endosomal escape agent, nigericin and (3) a chemically modified miRNA. The delivery ligand, DUPA (2-[3-(1,3-dicarboxy propyl) ureido] pentanedioic acid), was selected based on its specificity for prostate-specific membrane antigen (PSMA), a receptor routinely upregulated in prostate cancer-one of the leading causes of cancer death among men. DUPA was conjugated to the tumor suppressive miRNA, miR-34a (DUPA-miR-34a) based on the ability of miR-34a to inhibit prostate cancer cell proliferation. To mediate endosomal escape, nigericin was incorporated into the complex, resulting in DUPA-nigericin-miR-34a. Both DUPA-miR-34a and DUPA-nigericin-miR-34a specifically bound to, and were taken up by, PSMA-expressing cells in vitro and in vivo. And while both DUPA-miR-34a and DUPA-nigericin-miR-34a downregulated miR-34a target genes, only DUPA-nigericin-miR-34a decreased cell proliferation in vitro and delayed tumor growth in vivo. Tumor growth was further reduced using a fully modified version of miR-34a that has significantly increased stability.